Engineered bacterial cellulose-based Ag nanoparticles/g-C3N4/Eucalyptus extract nanocomposites for wound dressing: In vitro evaluation - Maral Sorourian; Mehrab Pourmadadi; Fatemeh Yazdian; Hamid Rashedi; Mona Navaei Nigjeh; Ghazal Sorourian; Abbas Rahdar; Sadanand Pandey (Elsevier, 2024)
In recent years, antibacterial wound dressings have gained considerable attention. Bacterial cellulose (BC) has received significant interest due to its unique physiochemical characteristics such as biocompatibility, high porosity, superior mechanical properties, water holding capacity, and nontoxicity. In this work, silver nanoparticles/graphitic carbon nitride/eucalyptus extract (Ag/gCN/EE) nanocomposite was synthesized as an antibacterial agent and incorporated into nanofibrous structures composed of BC. The BC/Ag/gCN/EE and polyvinyl alcohol/BC/Ag/gCN/EE (PVA/BC/Ag/gCN/EE) nanocomposites were synthesized using immersion and electrospinning methods, respectively. Then, the swelling ratio was optimized and the wound dressings were prepared based on the optimal formulation. The release profile, biodegradability and mechanical properties of the wound dressings were assessed. The antibacterial property of Ag/gCN/EE was studied demonstrating strong antibacterial activity on E. coli and S. aureus. MTT assay was carried out on NIH 3T3 fibroblast cells, and BC/Ag/gCN/EE and PVA/BC/Ag/gCN/EE nanocomposites showed 89 ± 2.31 % and 96 ± 3.28 % viability, respectively and no toxicity. To assess the effect of the composites on in vitro wound healing and cell migration, scratch wound assay was performed. The results indicated that after 24 h, BC/Ag/gCN/EE and PVA/BC/Ag/gCN/EE reduced 18.69 and 23.97 % of the scratch area compared to the control group. The prepared composites are promising wound dressings that could accelerate wound healing and kill bacteria simultaneously.